Assessing the practicality and appropriateness of focus group discussion (FGD) in takaful for construction research - Mohd Fauzi, Puteri Nur Farah Naadia; Abdul Rashid, Khairuddin (American Scientific Publishers, 2018)
Research in construction often adopt quantitative methodologies due to its nature that involves technology, which require strong evidence through hypothesis testing and presentation of results arising from mathematical and statistical analyses. However, there are research in construction that deal with issues concerning human behaviour, perceptions and opinions of the future, emotions and feelings that may not necessarily be technical. Therefore, for these types of construction research, qualitative methodologies are deemed to be more appropriate. This paper aims to assess the practicality and appropriateness of focus group discussion (FGD) in conducting takaful for construction research. The study combined two data sources that are (i) literature review, and (ii) a case study. Findings from the study suggest that the application of focus group discussion (FGD) is appropriate in (i) obtaining perceptions and emphasizing information for specific knowledge, and (ii) harmonizing opinions and gathering data from various groups of experts. Consequently, it is concluded that in the context of the present study the application of FGD is able to produce good, robust and reliable outcome and therefore its use is herein promoted in conducting construction research.